Individually preventive measures concerning offenses against human life and health in closed-type peni-tentiary institutions - Носенко, В’ячеслав Анатолійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article is dedicated to research of individual preventive measures concerning crimes against life and health in closed-type penitentiary institutions. Such measures include: identification of persons, whose actions and beliefs indicate a real possibility of committing such crimes; a comprehensive analysis of behavior of these individuals to determine the sources of negative impact on them; identification of opportunities to neutralize sources of negative influence on such persons and exploration options for preventing or stopping of criminal acts last in case preventive measures will not bring success; control of behavior of persons who are likely to commit these crimes, periodic inspections of results of undertaken preventive measures.